It’s true that the deduction theorem is not needed, as in the Wikipedia proof. I just like using the deduction theorem because I find it intuitive (assume A, prove B, then drop the assumption and conclude A→B) and it removes the need for lots of parentheses everywhere.
I’ll add a note about the meaning of ⊢ so folks don’t need to look it up, thanks for the feedback!
It’s true that the deduction theorem is not needed, as in the Wikipedia proof. I just like using the deduction theorem because I find it intuitive (assume A, prove B, then drop the assumption and conclude A→B) and it removes the need for lots of parentheses everywhere.
I’ll add a note about the meaning of ⊢ so folks don’t need to look it up, thanks for the feedback!
Thanks, that makes sense. And the added explanation helps a lot, I can see the argument for going from ⊢A→B to A⊢B now:
PA proves A→B;
So PA + A certainly proves A→B, since it can prove everything PA can;
Also, PA + A proves A;
So we have A⊢A∧(¬A∨B);
Which in turn gives us A⊢B.